Precipitation response to Heinrich Event-3 in the northern Indochina as revealed in a high-resolution speleothem record. Issue 7 (1st June 2022) - Nguyen, Dung Chi; Lee, Shih-Yu; Chen, Yue-Gau; Chiang, Hong-Wei; Shen, Chuan-Chou; Wang, Xianfeng; Doan, Lam Dinh; Lin, Yin
Highlights: The first high-resolution speleothem δ 18 O of the Heinrich Event 3 in Indochina. Detailed precipitation history is presented on the basis of dense and precise age controls. Both the onset and termination of the HE-3 event are characterized by gradual rather than abrupt progression. Precipitation change in tropical Indochina was attributed to the AMOC variation. Abstract: Heinrich Event-3 (HE-3) differs from other Heinrich Events (HEs) in terms of the strength of its expression in climatic records from different global localities. Here, we present new high resolution δ 18 O records from a composite speleothem record spanning from 31.5 to 28.4 ka within the HE-3 time interval. The record is obtained from two stalagmites collected from the Thuong Thien cave (TT), northern Vietnam, which exhibit growth rates of 0.12 to 0.68 mm/yr. The TT record shows a pronounced positive excursion of δ 18 O values of stalagmite in the time interval from 30.8 ka and lasted about one thousand years. Specifically, the δ 18 O reached maximum between ∼30.3–30.2 ka and returned to low values at 29.5 ka. Both the onset and termination phases of the excursion show gradual changes in δ 18 O values that form a relatively symmetric 'V' shape. The excursion suggests that the Indian Summer Monsoon (ISM), which modulates the climate and hydrology in the region, has endured dramatic weakening in response to HE-3. The timing and duration of the monsoonal decline are consistent with a significant slowdown of the Atlantic Meridional Ocean Circulation (AMOC), which probably drove the southward migration of the intertropical convergence zone (ITCZ) and consequently a decrease in precipitation over the Asian monsoonal region including northern Vietnam. To test the proposed mechanism, we further performed modeling simulations via an atmosphere general circulation model with a coupled slab ocean. Simulated results confirm both the scale and mechanistic connections between cooling in the North Atlantic and changes in precipitation at the Thuong Thien cave locality.